2012
DOI: 10.1007/s10072-012-1165-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and biological evaluation of chitosan–collagen–icariin composite scaffolds for neuronal regeneration

Abstract: In this study the chitosan/collagen/icariin composite scaffolds for nerve regeneration were produced by blending and crosslinking chitosan with collagen and icariin. The microstructure of the composite scaffolds was observed by scanning electron microscopy. 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide and attachment assays were conducted, respectively, to investigate the biocompatibility of the scaffolds. Cell cultural tests showed that the channel-structured porous scaffolds acted as a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Physical adsorption as a method to load the bioactive molecules and drugs onto the biomaterial scaffolds has been widely applied in previous studies [32][33][34]. This method has the advantages of ensuring the chemical structure and biological properties of the molecules, except for the inexpensive and efficacious characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Physical adsorption as a method to load the bioactive molecules and drugs onto the biomaterial scaffolds has been widely applied in previous studies [32][33][34]. This method has the advantages of ensuring the chemical structure and biological properties of the molecules, except for the inexpensive and efficacious characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a chitosan/collagen/icariin composite scaffold exhibited potential in nerve tissue engineering to promote proliferation and prolong neurite length in Schwann and PC12 cells[131].Icariin exhibited a strong capacity to protect cardiomyocytes or vein endothelium from harmful factors. It protected rat H9c2 cardiomyocytes from angiotensin II-induced hypertrophy and apoptosis by inhibiting the ROS-dependent JNK and p38 pathway[162].…”
mentioning
confidence: 99%
“…Icariin loaded porous β-tricalcium phosphate ce-128 ramic disks enhanced the proliferation and differentiation of Ros17/28 129 cells and new bone formation in vivo [151]. Icariin loaded cell-hydrogel 130 constructs improved the restoration efficiency of supercritical-sized 131 osteochondral defects in rabbit [38]. [42].…”
mentioning
confidence: 99%
“…ICA, the extract of traditional Chinese medicine-epimedium, has been proved as an osteoinductive agent for regeneration. Fan et al [23] and Yang et al [24] found that the combination of ICA and scaffold was biologically active and could promote the proliferation of osteoblasts in vitro bioactivity assay.…”
Section: Introductionmentioning
confidence: 98%